Subunit composition of VRAC channels determines substrate specificity and cellular resistance to Pt‐based anti‐cancer drugs. (3rd November 2015) - Planells‐Cases, Rosa; Lutter, Darius; Guyader, Charlotte; Gerhards, Nora M; Ullrich, Florian; Elger, Deborah A; Kucukosmanoglu, Asli; Xu, Guotai; Voss, Felizia K; Reincke, S Momsen; Stauber, Tobias; Blomen, Vincent A; et al.
Abstract: Although platinum‐based drugs are widely used chemotherapeutics for cancer treatment, the determinants of tumor cell responsiveness remain poorly understood. We show that the loss of subunits LRRC8A and LRRC8D of the heteromeric LRRC8 volume‐regulated anion channels (VRACs) increased resistance to clinically relevant cisplatin/carboplatin concentrations. Under isotonic conditions, about 50% of cisplatin uptake depended on LRRC8A and LRRC8D, but neither on LRRC8C nor on LRRC8E. Cell swelling strongly enhanced LRRC8‐dependent cisplatin uptake, bolstering the notion that cisplatin enters cells through VRAC. LRRC8A disruption also suppressed drug‐induced apoptosis independently from drug uptake, possibly by impairing VRAC‐dependent apoptotic cell volume decrease. Hence, by mediating cisplatin uptake and facilitating apoptosis, VRAC plays a dual role in the cellular drug response. Incorporation of the LRRC8D subunit into VRAC substantially increased its permeability for cisplatin and the cellular osmolyte taurine, indicating that LRRC8 proteins form the channel pore. Our work suggests that LRRC8D‐containing VRACs are crucial for cell volume regulation by an important organic osmolyte and may influence cisplatin/carboplatin responsiveness of tumors. Synopsis: LRRC8 proteins were recently shown to constitute the elusive volume‐regulated anion channel VRAC. This study shows that VRAC subunits LRRC8A and LRRC8D regulate both cell volume and uptake of anti‐cancer drugs, thus modulating cellular tumour drug responses. Substrate selectivity of the volume‐regulated anion channel VRAC depends on LRRC8 subunit composition, suggesting that these proteins form the channel pore. VRAC mediates cellular uptake of the cancer drugs cisplatin and carboplatin. By mediating drug uptake and by independently facilitating apoptosis, VRAC plays a dual role in tumor drug response. In addition to enabling cisplatin transport, LRRC8D facilitates cell volume regulation by the organic osmolyte taurine. Abstract : LRRC8 proteins were recently shown to constitute the elusive volume‐regulated anion channel VRAC. This study shows that VRAC subunits LRRC8A and LRRC8D regulate both cell volume and uptake of anti‐cancer drugs, thus modulating cellular tumour drug responses.